2018
DOI: 10.21776/ub.rjls.2018.005.03.1
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Time Spent for Internet Gaming, Grade Point Average and Internet Gaming Disorder Risk Among Medical Students

Abstract: The negative and positive consequences of internet games were less explored among medical students' population. The aim of this current study was to investigated the association between time spent for playing internet games and Grade Point Average (GPA) as well as Internet Gaming Disorder (IGD) risk among medical students. A total of 438 students in academic year 2016-2017 completed the self-report questionnaire, that covered socio-demographic information, GPA, time spent for internet gaming/day, and IGD scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Several factors with regards to the studies included could possibly explain this as well. Kurnianingsih et al ( 30 ) reported the lowest proportion of males (37.13%) but the highest prevalence of students with IGD (16.67%). This study had a large sample size of 438, which was around 19.6% of the total pooled sample size used.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several factors with regards to the studies included could possibly explain this as well. Kurnianingsih et al ( 30 ) reported the lowest proportion of males (37.13%) but the highest prevalence of students with IGD (16.67%). This study had a large sample size of 438, which was around 19.6% of the total pooled sample size used.…”
Section: Discussionmentioning
confidence: 96%
“…Meta-regression analysis found that age is not a significant moderator of prevalence rate of IGD in medical students and does not account for the heterogeneity in the pooled prevalence of IGD in medical students. However, Kurnianingsih et al (30) and Al Asqah et al (26) found that the prevalence of IGD was higher in the earlier years in medical school. Al Asqah et al (26) found that the majority (65%) of the students found to have IGD was from the 1st and 2nd years while Kurnianingsih et al (30) found that Year 1 medical students had the highest prevalence of IGD at 32%.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies in Indonesia have already described the prevalence, characteristics, and impacts of internet gaming disorder [9,18]. However, none of these studies focused on the relationship between internet gaming disorder and temperament, and internet gaming disorder and psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies in Indonesia have already revealed the prevalence, characteristics, and impacts of IGD [9], [12], [21], none of these studies focused on the relationship between IGD and cognitive function among adolescents, particularly in urban area. A recent study conducted among young adults in Korea showed that individuals with IGD had lower verbal comprehension, processing speed, and working memory compared with non-gamers [22].…”
Section: B -Clinical Sciences Neurologymentioning
confidence: 99%